Emergent trends in robotics and intelligent systems where is the role of intelligent technologies in the next generation of robots? - Sincak, Peter 1960- (Springer International Publishing, 2015)
What is the Role of Intelligent Technologies in the Next Generation of Robots? This monograph gives answers to this question and presents emergent trends of Intelligent Systems and Robotics. After an introductory chapter celebrating 70 years of publishing the McCulloch Pitts model, the book consists of the 2 parts Robotics" and Intelligent Systems" The aim of the book is to contribute to shifting conventional robotics in which the robots perform repetitive, pre-programmed tasks to its intelligent form, where robots possess new cognitive skills with the ability to learn and adapt to changing environment. The main focus is on Intelligent Systems, which show notable achievements in solving various problems in intelligent robotics. The book presents current trends and future directions bringing together Robotics and Computational Intelligence. The contributions include widespread experimental and theoretical results on intelligent robotics such as e.g. autonomous robotics, new robotic platforms, or talking robots.